PATENTES E ACESSO A MEDICAMENTOS: UMA COLISÃO DE DIREITOS FUNDAMENTAIS - Barbosa de Godoy Corrêa, Alexandra (2020)
This paper aims to approach industrial property as a fundamental right in order to generate insights on its implications in social life, as well as contributions to the development of a study about human rights to access medicines as a form of the right to health provided in the Federal Constitution of 1988. What is sought here is to discuss whether or not there is compatibility between the right to access medicines and the right to pharmaceutical patents, since under international order both are human rights and, regarding the national order, they are fundamental rights. Thus, it can be concluded that it is important to combine state obligations with the need for sustainable development, that is, to encourage innovation as an element of sanitation of the problem of medicines access, without thereby disrespecting the right to pharmaceutical patents.